2020
DOI: 10.3390/nu12092770
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Running Enhances NF-κB Activity in the Mice Liver and the Intervention Effects of Quercetin

Abstract: Background: Emerging evidence has supported that intensive exercise induces weakened performance and immune and metabolic disorders. We systematically evaluated the effects of quercetin against hepatic inflammatory damage caused by repeated intensive exercise and explored the potential mechanism. Methods: Male BALB/c mice were administered quercetin (100 mg/kg BW) for four weeks, and performed a treadmill running protocol of 28 m/min, 5° slope, 90 min/day concurrently for the last seven days. Results: Querceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Pro-inflammatory cytokines and anti-inflammatory cytokines play a central role in the modulation of the intestinal immune system, and inflammatory cytokines can be used to assess the inflammation level. , Moreover, NF-κB inhibition is required for the decrease in epithelial TJs permeability, which suggests that NF-κB signaling is a potential therapeutic target for the treatment of intestinal inflammation . In addition, NF-κB in intestinal tissue could be activated by 5-Fu, and it further induced the gene expression of pro-inflammatory cytokines such as IL-1β and IL-6 , leading to the destruction of intestinal barrier function. , QUE plays a significant role to promote the expression of anti-inflammatory cytokines such as IL-10 . The inflammation-related mRNA in the jejunum and colon was analyzed for the C, 5-Fu, QUE-CDNPs, QUE, and CDNPs groups (Figure C–F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro-inflammatory cytokines and anti-inflammatory cytokines play a central role in the modulation of the intestinal immune system, and inflammatory cytokines can be used to assess the inflammation level. , Moreover, NF-κB inhibition is required for the decrease in epithelial TJs permeability, which suggests that NF-κB signaling is a potential therapeutic target for the treatment of intestinal inflammation . In addition, NF-κB in intestinal tissue could be activated by 5-Fu, and it further induced the gene expression of pro-inflammatory cytokines such as IL-1β and IL-6 , leading to the destruction of intestinal barrier function. , QUE plays a significant role to promote the expression of anti-inflammatory cytokines such as IL-10 . The inflammation-related mRNA in the jejunum and colon was analyzed for the C, 5-Fu, QUE-CDNPs, QUE, and CDNPs groups (Figure C–F).…”
Section: Resultsmentioning
confidence: 99%
“…Nanoscale carriers encapsulating natural compounds have been designed and used for effective delivery. Encapsulating the compounds within nanoliposomes or polymer nanoparticles can result in visible improvement in the above-mentioned unfavorable properties. , Polymer nanoparticles, such as a nano-sized hydrogel, whose three-dimensional network properties are similar to those of intestinal mucosa matrix, have received considerable interest . However, the potential toxicity associated with delivery materials poses additional limitations; therefore, the utilization of food-grade polymer nanoparticles encapsulating QUE is a promising approach to enhance therapeutic efficacy compared with the corresponding unencapsulated compounds in various animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…This flavonoid compound is found in many foods and herbs, including daily foods such as green beans, tomatoes, grapes, and apples, as well as herbs such as ginkgo, milk thistle, etc (Brito, Lima, Cordeiro, & da Cruz Nizer, 2021). Quercetin can not only improve human metabolism and reduce sports injury through the IL‐6/NF‐kB pathway (Gao et al, 2020), but also regulate the activation of the IL‐6/STAT3 pathway, thus achieving antiinflammatory, antioxidative, anticancer, and anti‐allergy effects (“Quercetin,” 2012).…”
Section: Phenolic Compounds That Mediate the Effects Of Il‐6 On Tumorsmentioning
confidence: 99%
“…Hepatocytes are rich in glycogen, which is an essential nutrient during intense exercise in consistently providing energy; at the same time, hepatocytes are also rich in mitochondria, which can generate amounts of ATP efficiently through the oxidative phosphorylation process for the cellular requirement. Studies have shown that vigorous exercise can cause acute liver injury characterized by alterations of liver enzymes in the serum [ 6 ], and liver morphological abnormality, oxidative stress, and inflammation were also detected in exhaustive exercise models of animals [ 7 ]. However, the mechanisms and potential targets underlying vigorous exercise-caused liver damage are still unclear; thus, there is a lack of prevention and treatment means.…”
Section: Introductionmentioning
confidence: 99%